Evolution of Aerosol Vertical Distribution During Particulate Pollution Events in Shanghai - 张云伟 张群 冷春鹏 张德芹 成天涛 陶俊 张仁健 贺千山 (Journal of Meteorological Research, 2015)
A set of micro pulse lidar （MPL） systems operating at 532 nm was used for ground-based observation of aerosols in Shanghai in 2011. Three typical particulate pollution events （e.g., haze） were examined to determine the evolution of aerosol vertical distribution and the planetary boundary layer （PBL） during these pollution episodes. The aerosol vertical extinction coefficient （VEC） at any given measured altitude was prominently larger during haze periods than that before or after the associated event. Aerosols originating from various source regions exerted forcing to some extent on aerosol loading and vertical layering, leading to different aerosol vertical distribution structures. Aerosol VECs were always maximized near the surface owing to the potential influence of local pollutant emissions. Several peaks in aerosol VECs were found at altitudes above 1 km during the dust- and bioburningoinfluenced haze events. Aerosol VECs decreased with increasing altitude during the local-polluted haze event, with a single maximum in the surface atmosphere. PM2.5 increased slowly while PBL and visibility decreased gradually in the early stages of haze events; subsequently, PM2.5 accumulated and was exacerbated until serious pollution bursts occurred in the middle and later stages. The results reveal that aerosols from different sources impact aerosol vertical distributions in the atmosphere and that the relationship between PBL and pollutant loadings may play an important role in the formation of pollution.